2021
DOI: 10.3389/fpsyg.2021.553963
|View full text |Cite
|
Sign up to set email alerts
|

Female Entrepreneurial Intentions in Pakistan: A Theory of Planned Behavior Perspective

Abstract: With theoretical underpinnings in the theory of planned behavior, this research aims at investigating how women's entrepreneurial intentions might develop in Pakistan. The survey of 216 female students revealed that psychological capital plays an important role in shaping women's entrepreneurial commitment which in turn results in increased intentions to opt for entrepreneurship as a career. Additionally, it was observed that social support moderates the indirect relation in such a way that in the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 139 publications
0
14
0
Order By: Relevance
“…Usually, women face significant opposition when establishing their own business, which leads to the perception that considered as food provider instead of food creators [ 3 ]. As women encounter increasing obstacle to careers that pay, motivation and encouragement may enhance their performance in business intentions because they represent unexploited assets that can be used to improve a country’s economic prospects [ 4 ]. Some studies found that obtaining and using the enterprise economy relies on women’s entrepreneurship growth [ 2 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Usually, women face significant opposition when establishing their own business, which leads to the perception that considered as food provider instead of food creators [ 3 ]. As women encounter increasing obstacle to careers that pay, motivation and encouragement may enhance their performance in business intentions because they represent unexploited assets that can be used to improve a country’s economic prospects [ 4 ]. Some studies found that obtaining and using the enterprise economy relies on women’s entrepreneurship growth [ 2 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Responses were recorded on the five point Likert type scale ranging from 1 (strongly disagree) to 5 (strongly agree). EI is a reliable and valid measure having excellent internal consistency of 0.89 and has been frequently used by researchers in Pakistan ( Anjum et al, 2018b ; Sarwar et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…[46] applied TPB to explain about the changes of attitudes of entrepreneurs in Singapore in term of intention to become entrepreneur before and post COVID. Same goes to TPB also been used in the study by [17] [47] that look at how the women entrepreneur's intention develop in Pakistan and in Thailand focusing hospitality industry [48].…”
Section: B Institutional Theorymentioning
confidence: 99%